2018
DOI: 10.1101/314880
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global emergence and population dynamics of divergent serotype 3 CC180 pneumococci

Abstract: Streptococcus pneumoniae serotype 3 remains a significant cause of morbidity and mortality worldwide, despite inclusion in the 13-valent pneumococcal conjugate vaccine (PCV13). Serotype 3 increased in carriage since the implementation of PCV13 in the United States, while invasive disease rates remain unchanged. We investigated the persistence of serotype 3 in carriage and disease, through genomic analyses of a global sample of 301 serotype 3 isolates of the Netherlands 3 -31 (PMEN31) clone CC180, combined with… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 69 publications
1
14
0
Order By: Relevance
“…A coherent hypothesis for PCV13 impact on serotype 3 should take into account all of these data: substantial direct protection; evidence of overall reductions in population-based incidence in the early, but not later, years following introduction; and lower protection afforded by PCV13 against serotype 3 relative to other vaccine serotypes. A recent study has also suggested that there has been a genetic shift from a relatively low to a relatively high antibiotic-resistant serotype 3 clade that was not driven by PCV13 use [43]. One possible explanation that incorporates these observations is that PCV13 provides direct protection against disease and, to a lower extent, carriage.…”
Section: Discussionmentioning
confidence: 99%
“…A coherent hypothesis for PCV13 impact on serotype 3 should take into account all of these data: substantial direct protection; evidence of overall reductions in population-based incidence in the early, but not later, years following introduction; and lower protection afforded by PCV13 against serotype 3 relative to other vaccine serotypes. A recent study has also suggested that there has been a genetic shift from a relatively low to a relatively high antibiotic-resistant serotype 3 clade that was not driven by PCV13 use [43]. One possible explanation that incorporates these observations is that PCV13 provides direct protection against disease and, to a lower extent, carriage.…”
Section: Discussionmentioning
confidence: 99%
“…Serotype 3 also causes considerable disease burden [11,27] being the most common overall cause of pneumonia in the USA [34], is highly invasive [28] and is associated with increased mortality [29]. Distinct lineages exist within serotype 3 clonal complex 180, and recent clade distributions shift has led to the emergence and expansion of clade II [35,36], which now represents 50% serotype 3 IPD in the UK [37]. We could not determine serotype 3 clade grouping in this analysis, but clade II emergence may, at least in part, explain serotype 3 disease persistence.…”
Section: Discussionmentioning
confidence: 99%
“…A major strength of this work is the use of a locally-relevant and globally-important invasive pneumococcal ST3. ST3 is among the commonest pneumococcal carriage serotypes in Malawi ( 7 ) and is also a global concern due to the persistent ST3 disease ( 7 , 10 , 11 ). Pneumococcal ST3 is biochemically different from the other serotypes, having a large thick polysaccharide capsule, surrounded by a slime layer, which gives it a characteristic mucoid appearance when grown on blood agar plates ( 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Globally, pneumococcus serotype 3 (ST3) is of major concern, since effectiveness of the pneumococcal conjugate vaccines (PCV) against it remain uncertain. Specifically, there is limited reduction in ST3 disease compared to the other vaccine serotypes in the era of PCV ( 7 , 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%